Advancements in Regenerative Medicine for Articular Cartilage Repair in the Management of Osteoarthritis: A Review of Modern Treatment Methods - Dziewic, Jakub; Przygoda, Maria; Śnieżna, Joanna; Trestka, Gabriela; Stępień, Kamila; Adamczyk, Sabina; Zelik, Urszula; Florczak, Wojciech; Domino, Wiktoria; Włodyka, Jagienka; Dzwonnik, Karol (Quality in Sport, 2025)
Osteoarthritis (OA) is the most common form of chronic joint diseases, and its treatment still remains difficult with the current state of medicine. In this review, modern regenerative methods used in the repair of articular cartilage, both traditional techniques and innovative cellular therapies, are described. It focuses on the most updated treatment modalities, discussing, among other methods, microfracture, osteochondral grafts, autologous chondrocyte implantation (ACI), novel approaches of matrix-assisted autologous chondrocyte transplantation (MACT) and mesenchymal stem cell (MSC) treatments, with especial regard toward the use of platelet-rich plasma (PRP) in relation to other intra-articular injections, namely hyaluronic acid and ozone therapy. The regenerative treatments analyzed in this review have great potential in cartilage defect repair and possible symptom alleviation for OA; long-term efficacy, however, and limitations of cost and invasiveness do have to be more extensively considered. Another discussion concerns macrophages, modulators of the inflammatory environment of the joint, and whether they could serve as potential therapeutic targets. The need for further investigation, in order to modify the existing methods and create other effective regenerative approaches in patients suffering from OA, is presented.